2013
DOI: 10.1016/j.atherosclerosis.2013.07.045
|View full text |Cite
|
Sign up to set email alerts
|

The association between physical activity and both incident coronary artery calcification and ankle brachial index progression: The Multi-Ethnic Study of Atherosclerosis

Abstract: Objective Both coronary artery calcification (CAC) and the ankle brachial index (ABI) are measures of subclinical atherosclerotic disease. The influence of physical activity on the longitudinal change in these measures remains unclear. To assess this we examined the association between these measures and self-reported physical activity in the Multi-Ethnic Study of Atherosclerosis (MESA). Methods At baseline, the MESA participants were free of clinically evident cardiovascular disease. We included all partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 39 publications
4
58
2
1
Order By: Relevance
“…This is a novel finding in patients with CKD-5D but in agreement with results in subjects without CKD. 31 Use of DXA for measurement of BMD has been considered of limited usefulness for patients with CKD. 32,33 This was mostly related to the occurrence of extraosseous calcifications that might be included in the measurement results.…”
Section: Discussionmentioning
confidence: 99%
“…This is a novel finding in patients with CKD-5D but in agreement with results in subjects without CKD. 31 Use of DXA for measurement of BMD has been considered of limited usefulness for patients with CKD. 32,33 This was mostly related to the occurrence of extraosseous calcifications that might be included in the measurement results.…”
Section: Discussionmentioning
confidence: 99%
“…35 Lower physical activity also predicts progression of PAD with greater decline in the ABI over time. 36 Thus, therapeutic approaches that restore functional capacity in patients with PAD may have a wide-ranging health-promoting effect.…”
Section: Global Epidemiology Of Padmentioning
confidence: 99%
“…The results of the Multi-Ethnic Study of Atherosclerosis suggested that sedentary behavior can increase the progression of coronary disease once it is present and that any type of activity is better than sedentary behavior for patients with early coronary artery disease. 18 Compared with participants with mild and moderate cardiovascular risk, those with severe cardiovascular risk were able to cover shorter distances during the 6-minute walk test, although a significant difference was only observed for the total distances covered by men. Previous studies demonstrated that self-reported ability to walk using the Walking Impaired Questionnaire (WIQ) was associated with or predicted cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 96%